Clinical Encounters and Treatment Initiation for Chronic Hepatitis C Patients: Applications of Adaptive Leadership Framework for Chronic Illness. (January 2019) - Bailey, Donald E.; Muir, Andrew J.; Adams, Judith A.; Thygeson, N. Marcus; Williams, Hants; Cary, Michael P.; Anderson, Ruth A.
Chronic hepatitis C (CHC) is the most common blood-borne infection in the United States. Patients with CHC undergoing treatment face many challenges including adherence to medications and management of symptoms; health care practitioners are well positioned to facilitate patients' ability to address these challenges. We used the Adaptive Leadership for Chronic Illness Framework to investigate the difficulties inherent in affecting behavior change in patients undergoing treatment. We enrolled 11 patient participants and 10 provider participants. We used data from the first clinical encounter between patients and providers during which treatment was discussed. We found examples of adaptive leadership and categorized these behaviors into three themes: support for medication, coping with family/home life, and strategizing to manage employment. We also saw examples of what we termed missed opportunities for adaptive leadership. This study illustrates the contributions of adaptive leadership behaviors by health care providers and the potential risk to patients in their absence.